Technology Portfolio Planning and Management Practical Concepts and Tools - Yu, Oliver (International Series in Operations Research & Management Science,, 2006)
From the large overall scope of planning and management of technology, TECHNOLOGY PORTFOLIO PLANNING AND MANAGEMENT: Practical Concepts and Tools focuses specifically on the concepts and tools for the planning and management of an investment portfolio by a government or a business organization for either the development or the application of technologies. A portfolio is a coordinated combination of technologies that achieve a common objective for the decision-maker. Thus, the book will focus on those concepts and tools for selecting and modifying such a combination of technologies that will be either developed by a technology supply organization, such as a national laboratory or a corporate research center, or adopted by a technology application organization, such as a government administrative office or a corporation management department, to either advance public goals (such as space exploration or disease eradication) or enhance corporate strategies (such as improving productivity or increasing competitiveness). In addition, many concepts and tools to be discussed in this book are well-established technical disciplines of their own: Analytic Hierarchy Process, Expected Utility Theory, Time Series Forecasting, Scenario Planning, Linear Programming, Dynamic Programming, Decision Tree Analysis, Real Options Theory, and Project Evaluation and Review Technique. The purpose of this book is to utilize the basic principles and practical applications aspects of these concepts and tools that are particularly relevant to technology portfolio planning and management. ****************************************************************************** "Dr. Yu is a recognized expert in technology management. His book is a wonderful summary of many important concepts and tools developed from his rich experience. It is full of useful gems of practical wisdom. It is a book that emphasizes the basic principles and practical methods of technology portfolio planning and management, rather than convoluted theory and obscure analysis. I heartily recommend it to both students and practitioners of technology management." Dr. Mitsuho Uchida, Associated Vice President, Central Research Institute for Electric Power Industry, Japan "Dr. Yu is a well-known expert in technology management. His new book on technology portfolio planning and management is a welcome addition. By presenting many practical concepts and tools and their respective advantages and disadvantages, it will be an important textbook as well as toolbook." Mr. T.C. Tu, Director, Industrial Economics and Foresight Department, Industrial Technology Research Institute, Taiwan "There is a shortage of usable textbooks. Dr. Yu's book is a timely fill of the void. Being a seasoned practitioner of technology portfolio planning and management, Dr. Yu has emphasized principles that can serve as the starting point for additional research. Thus, we have eagerly anticipated his book. Even before its publication, we have used sections from the manuscript of the book, including scenario forecasting, decision tree analysis, and real options analysis, for the technology management courses." Dr. Hisatoshi Yamamoto, Professor of Technology Management, Tokyo University and Waseda University "I think the book is very good and will be useful in defining the approaches and tools that can be used to evaluate the mix of technology investments that will yield the optimal allocation of resources to achieve a desired outcome." Mr. Richard Rudman, Executive Vice President, Electric Power Research Institute, Palo Alto, California .